2018
DOI: 10.5114/amsad.2018.81000
|View full text |Cite
|
Sign up to set email alerts
|

Autogenously derived regenerative cell therapy for venous leg ulcers

Abstract: IntroductionVenous leg ulcers (VLUs), which arise from chronic venous insufficiency in the lower limbs, are a major cause of morbidity and significantly negatively impact patients’ health-related quality of life. Treatment of venous ulcers can be either conservative or surgical. Despite appropriate treatment, VLUs can be resistant to healing. Clinical results of treatment of venous foot ulcers with adipose-derived autologous stem cells, which did not improve despite the surgical treatment of the underlying ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…Venous ulcer is a common vascular pathology affecting 1% of the population, and its prevalence increases with age [15,16]. Superficial, perforating, or deep vein insufficiency are risk factors for venous ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…Venous ulcer is a common vascular pathology affecting 1% of the population, and its prevalence increases with age [15,16]. Superficial, perforating, or deep vein insufficiency are risk factors for venous ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the efficacy of stem-cell therapies for a variety of wounds, including burns, non-healing ulcers, and critical limb ischemia [90][91][92][93][94][95][96]. A systematic review published in 2020 that investigated the clinical application of stem-cell therapy for the treatment of chronic wounds showed the potential of a variety of stem cells in the restoration of impaired wound healing, both in vitro and in vivo, despite the clinical evidence being very limited.…”
Section: Stem-cell Therapiesmentioning
confidence: 99%
“…ADSCs are easy to obtain due to lower morbidity during the harvesting procedure[ 78 , 80 ], can be implanted at the wound site immediately following debridement, and promote a new tissue formation rich in vascular structures and remodeling collagen[ 82 ]. As an additional treatment to primary surgical therapy for CVLUs[ 83 ], one study showed that it does not shorten the venous recovery period but decreases the 1-year recurrence rate[ 83 ]. However, preclinical and observational RCT reports indicate that centrifuged adipose tissue containing progenitor cells is safe and may accelerate healing time in CVLUs and reduce wound pain[ 84 ].…”
Section: Adipose-derived Mscsmentioning
confidence: 99%